Analisis Ekspresif Lirik Lagu “Rayuan Perempuan Gila” Karya Nadin Amizah: Pendekatan Pragmatik - Mutia Rahmah (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2025)
This research analyzes the lyrics of the song "Rayuan Perempuan Gila" by Nadin Amizah using an expressive and pragmatic approach. The expressive approach focuses on expressing the songwriter's emotions, feelings and personal views, while the pragmatic approach emphasizes the communication function of the lyrics to the listener. The research was conducted using qualitative descriptive methods with literature study techniques and analysis of illocutionary speech acts. The research results show that the lyrics of this song contain various types of speech acts, namely assertive, directive, commissive, expressive and declarative. Assertive speech acts are used to emphasize the truth, directive to ask for a response from the listener, commissive to express promises or commitments, expressive to express emotions such as fear, and declarative to create new meaning through specific naming. Through this speech act, interesting communication is created between the author and the listener, so that the moral message about the importance of loving oneself and understanding the dynamics of social relationships is conveyed well. This research contributes to understanding how song lyrics can be a medium for self-expression.